Vaccinating Britain Mass vaccination and the public since the Second World War - Millward, Gareth (Social Histories of Medicine, 2019)
Vaccinating Britain shows how the British public has played a central role in the development of vaccination policy since the Second World War. It explores the relationship between the public and public health through five key vaccines - diphtheria, smallpox, poliomyelitis, whooping cough and measles-mumps-rubella (MMR). It reveals that while the British public has embraced vaccination as a safe, effective and cost-efficient form of preventative medicine, demand for vaccination and trust in the authorities that provide it has ebbed and flowed according to historical circumstances. It is the first book to offer a long-term perspective on vaccination across different vaccine types. This history provides context for students and researchers interested in present-day controversies surrounding public health immunisation programmes. Historians of the post-war British welfare state will find valuable insight into changing public attitudes towards institutions of government and vice versa.